Contextualising Law: An Attempt to Operationalise Theory by Teaching Interviewing in the Law School - Alan Leaver (Legal Education Review)
In the Pearce Report three major goals of law schools were identified as similar to those of universities: to undertake research; to service the community; and to teach.1 Achievement of the last goal required going beyond the mere “imparting of knowledge” to include (among other things) an understanding of the law in operation as well as in context, and to develop in students practical legal skills and competencies that were essential to all types of legal work, notwithstanding the degree of separation of that work from the practice of law.2 The recommendation was made that this objective could be achieved by teaching specific practical legal skills such as advocacy, communication, counselling, drafting, interpretation of legislation, negotiation, and research and writing.3 One inference to be drawn from the above recommendation is that the teaching of law can be improved, and the perceived separation of the theory and the practice of law narrowed to some extent, by incorporating practical legal skills into the curricula of law schools. This hypothesis, that teaching and learning of law can be optimised by creating and maintaining a substantial and realistic nexus between legal theory and legal practice,4 finds support from recent research in general educational theory and methodology of other practice-based professions.5 However, research in Australia to support that hypothesis in regard to law in the interim since the publication of the Pearce Report appears to remain limited if special issues of periodicals,6 specialist periodicals7 and projects supported by the Committee for the Advancement of University Teaching8 can be relied upon as indicators of research. This alleged limitation exists notwithstanding attention being brought by the Pearce Report to the relative paucity of writing, and to the almost absolute absence of empirical data, on legal education.9 A movement towards incorporation of such a practical approach, endorsed at the time of publication of the Pearce Report by some commentators10 and subsequently supported by others,11 has occurred since the release of the Pearce Report, especially in newly established law schools which have been innovative to varying degrees,12 thanks in part to support from the Committee for the Advancement of University Teaching. This paper describes one such innovation in legal education, the teaching of interviewing skills as an addition to the mooting component of the criminal law course, adopted at the Law School of the Flinders University of South Australia and supported by a grant from the Committee for the Advancement of University Teaching during 1994. The mooting framework of the criminal law curriculum into which the interviewing project was placed is detailed before outlining the educational theory that justifies the choice of interviewing. The interviewing project is then briefly described.